MERANCANG MODEL LATIHAN MENYIMAK BERBAHASA INGGRIS BAGI SISWA KELAS 12 - Liliek Soepriatmadji (Universitas Stikubank (UNISBANK) Semarang, 2016)
This study is aimed at (1) construing qualitatively the need for developing of alistening model for their twelfth graders; (2) designing a listening model whichcould be attached to a web – e-learning system. The researchers also quantitativelyanalyze the index of difficulty and that of discriminating power; (3) construing theresponses of the English teachers and their twelfth graders towards the designedlistening model. The results indicate that teachers really need a listening modeldesigned on the bases of the present curriculum. Secondly, the model can beimplementable and executable though with moderate difficulty index and low indexof discriminating power. Finally, it is known that the English teachers display theirpositive attitude towards the model. However, the twelfth graders do not indicatetheir positive attitude towards it.Key words: listening model, e-learning, discriminating power, index of difficultylevel